Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode Risk-Based Bank Rating (RBBR) (Studi Pada Bank yang Termasuk Saham LQ45 Sub Sektor Perbankan Tahun 2010–2016) - Bobby Wijaya (Universitas Kristen Maranatha, 2018)
This paper seeks to find out the health level of banks in Indonesia Stock Exchange LQ45 Index. It used descriptive methods with qualitative approach that is Risk Based Bank Rating (RBBR) model. RBBR model consists of 4 factors among others: risk profile, good corporate governance (GCG), earnings and capital factor.The analytical tool used in this study is the assessment of the level of health of banks in Indonesia Stock Exchange LQ45 Index against the risk factor using the ratio of net performing loans (NPLs) and Loan to Deposit Ratio (LDR), a factor of corporate governance by using the self-assessment report of good corporate governance, the earnings factor using the ratio of return on assets (ROA) and net interest margin (NIM) and the factor of capital using the ratio of capital adequacy ratio (CAR). The results showed that there are several banks which have